AB0389 GLUCOCORTICOID WITHDRAWAL IN SYSTEMIC LUPUS ERYTHEMATOSUS: ANALYSIS OF 750 SLE PATIENTS FROM THE RUSSIAN AND KYRGYZ COHORTS. (2nd June 2020) - Solovyev, S.; Aseeva, E.; Koilubaeva, G.; Nasonov, E.; Lila, A.; Nikishina, N.
Abstract : Background: Objectives: Glucocorticoids (GCs) have been the mainstream of systemic lupus erythematosus (SLE) treatment for the last 70 years. GCs allow to achieve effective control over SLE activity quite rapidly – both in mild and severe disease. The majority of SLE patients have received GC therapy; in some cohorts up to 80% - 100% of patients continue on low maintenance GCs doses < 7.5 mg/day for many years, perhaps some of them are treated indefinitely. It is clear that cumulative GCs dose is responsible for adverse effects. But it remains still unclear whether GCs should be continued indefinitely and, if not, when and how this treatment should be discontinued. On the other hand, treat-to-target SLE recommendations suggest GC withdrawal where possible as an important target of the treatment plan. Methods: Patients who attempted GCs withdrawal were included in the Eurasian SLE RENAISSANCE cohort. A retrospective analysis of 350 patients from Russia and 400 patients from Kyrgyzstan was conducted. The following information was assessed during withdrawal attempts: SLE duration, disease activity at the onset and initiation of GCs dose reduction, therapy at SLE onset, the duration of the last flare, activity and therapy at the end of FUP, and duration of remission after GCs withdrawal. Definitions of remission were applied to GCs withdrawal in line with European consensus criteria. Results: Out of 750 patients with a follow-up of about 6 years (IQR 1-23), GCs withdrawal due to persistent remission was documented in 15 patients (2.0%). In 14 out of these 15, SLE onset was associated with high disease activity based on SLEDAI 2K > 8. High level of anti-DNA and a decrease in C3 C4 complement were present in 12, 4 patients had nephritis with preserved renal function, 4 patients manifested signs of CNS damage (convulsions, headaches, sleep disturbances, memory issues, neuropathy, hallucinations), and another 5 had vasculitis. 10 patients were administered pulse therapy with 3 g methylprednisolone due to high disease activity. Initiation of GCs dose reduction with intent to discontinue in 7 patients was substantiated by prolonged clinical remission, meanwhile SLE duration in this group varied from 2 to 20 years, and duration of the last flare - from 6 to 165 months. Acute onset with high disease activity reaching 12-23 scores by SLEDAI 2 K was documented in 8 cases of early SLE with disease duration varying from 1.5 to 6 months. These patients were prescribed the most aggressive induction therapy, including cascade plasma filtration in combination with pulse therapy, cyclophosphamide and Rituximab at 1 g dose. Remission (SLEDAI2K 0-2 scores) was achieved 4-6-8 months later after termination of aggressive induction therapy. The duration of remission after GCs withdrawal in all 15 patients ranged from 3.5 to 240 months. In 8 patients with aggressive induction therapy, remission lasted from 18 to 240 months. In 2 remaining patients, remission lasted for 9 and 16 months after GCs withdrawal. Each flare required intake of low prednisolone doses for 3-4 weeks. Conclusion: GCs withdrawal is an achievable goal in SLE and may be attempted after a long-term remission, and possibly after aggressive intensive care in the early stages of SLE. Disclosure of Interests: None declared